Study on Electrochromic Execution of Nickel Oxide Thin Films Prepared by Sol-Gel Route: Investigating the properties and performance of NiO thin films prepared through sol-gel process (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Nanostructure metal oxide films has produced enthusiasm throughout the years because of their wide application (Ahuja D, Tatsutani M. 2009). They are utilized in radiation detectors, sun oriented cells, semiconducting gadgets, laser materials, thermoelectric device, and optoelectronic devices. Nanostructured metal oxide is a promising alternative for thin film sun oriented cells. NiO is one such metal oxide with numerous reasonable properties. The NiO thin films were portrayed for their auxiliary, compositional, morphological, electro chromic, optical and colorimetric properties utilizing X-beam diffraction, X-Ray photoelectron spectroscopy (XPS), Scanning electron microscopy (SEM), FT-IR spectroscopy, cyclic voltammetry (CV), and optical transmittance and CIE arrangement of colorimetric estimations separately. The present study manages the readiness of NiO thin films by utilizing basic and minimal effort sol-gel plunge covering and its electro chromic execution.